A highly weatherable silicone hydrogel contact lens material and method of making the same

CN120699208BActive Publication Date: 2026-10-20IRIS (XIAMEN) TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510787305.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-13
Publication Date
2026-10-20
Estimated Expiration
2045-06-13

AI Technical Summary

Benefits of technology

本申请选用3-[三(三甲基硅氧基)硅基]丙基乙烯基氨基甲酸酯、乙烯基三异丙烯氧基硅烷和聚二甲基硅氧烷单甲基丙烯酸酯三种聚硅基单体,3-[三(三甲基硅氧基)硅基]丙基乙烯基氨基甲酸酯分子中含三个三甲基硅氧基,硅氧链段提供连续的氧气传输通道,提升材料透氧系数。氨基甲酸酯基团增强硅氧烷与其他单体的相容性,减少相分离,乙烯基三异丙烯氧基硅烷作为交联增强剂,三个异丙氧基在水解后形成硅醇基,可与其他硅基单体或纳米粒子发生缩合反应,形成三维交联结构,提升材料力学性能,并且异丙氧基水解后的硅氧交联网络疏水性较强,减少镜片在水中的溶胀率,保持尺寸稳定性。聚二甲基硅氧烷单甲基丙烯酸酯三种聚硅基单体作为柔性链段,长链聚二甲基硅氧烷赋予材料柔韧性,降低刚性,改善佩戴舒适度。并且聚二甲基硅氧烷链段倾向于向材料表面迁移,形成低表面能的硅氧烷层,减少蛋白质吸附和沉积物,提升抗污性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of contact lens material preparation, in particular to a high-weather-resistance silicon hydrogel contact lens material and a preparation method thereof. The preparation method of the contact lens material is as follows: step S1, adding polymerization monomers, weather-resistant additives and functional additives into anhydrous ethanol, stirring in the dark to obtain a premixed solution; step S2, adding nano-silver and nano-titanium dioxide into the premixed solution, carrying out ultrasonic dispersion, adding a crosslinking agent and an initiator, uniformly mixing, pouring into a contact lens mold, carrying out photo-induced polymerization under the protection of inert gas, washing with deionized water, balancing with boric acid buffer to obtain the high-weather-resistance silicon hydrogel contact lens material. The prepared contact lens material not only has high oxygen permeability and high light transmittance, can effectively guarantee that the cornea obtains sufficient oxygen, and has excellent weather resistance and is not easy to deform or be damaged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of contact lens material preparation technology, specifically to a high weather-resistant silicone hydrogel contact lens material and its preparation method. Background Technology

[0002] Contact lenses are important medical devices for vision correction and cosmetic purposes. Silicone hydrogel has become the mainstream material for modern contact lenses due to its ultra-high oxygen permeability. The core advantage of this material comes from the siloxane segments introduced into its molecular structure, which can directly deliver oxygen through the dissolution and diffusion mechanism, significantly reducing the risk of complications such as corneal hypoxia-induced edema and neovascularization.

[0003] However, while the siloxane components in traditional silicone hydrogel materials can significantly improve oxygen permeability, their hydrophobicity reduces the material's hydrophilicity, resulting in insufficient wettability of the lens surface and easily causing dry eye discomfort. To balance this contradiction, conventional solutions require the introduction of a high proportion of hydrophilic monomers, but this leads to a decrease in cross-linking density and a loose network structure. Rapid evaporation of water causes gel shrinkage and deformation. Secondly, lipids and proteins in tears are easily adsorbed onto the lens surface to form biofilms. Traditional silicone hydrogels are rich in siloxane microregions on the surface, making it easy for deposits to accumulate. This not only causes blurred vision and irritation but also becomes a breeding ground for microorganisms, increasing the risk of keratitis. In addition, ultraviolet radiation and thermal oxidation are key environmental factors that cause material aging. Ultraviolet radiation can cause the cleavage of the siloxane backbone and the degradation of aromatic ultraviolet absorbers, resulting in decreased light transmittance and yellowing of the lens. Thermal oxidation reaction leads to the breakage of the cross-linked network, which manifests as permanent hardening of the material and decreased oxygen permeability. Traditional silicone hydrogel materials have significant limitations in terms of long-term stability, anti-deposition and mechanical durability. Based on the above defects, this application provides a high weather-resistant silicone hydrogel contact lens material and its preparation method, which can be used to prepare silicone hydrogel contact lenses with high oxygen permeability, comfortable wearing experience and weather resistance. Summary of the Invention

[0004] To address the technical problems mentioned in the background section, this application provides a high weather-resistant silicone hydrogel contact lens material and its preparation method.

[0005] A method for preparing a highly weather-resistant silicone hydrogel contact lens material includes the following preparation steps: Step S1: Add the polymer monomer, weather-resistant additive, and functional additive to anhydrous ethanol, stir in the dark for 1-2 hours, and after stirring evenly, obtain the premixed solution. Step S2: Add nano-silver and nano-titanium dioxide to the premixed solution, disperse by ultrasonication, add crosslinking agent and initiator, mix evenly, inject into contact lens mold, carry out photo-initiated polymerization reaction under inert gas protection, wash with deionized water, and equilibrate with borate buffer to obtain high weather-resistant silicone hydrogel contact lens material.

[0006] Preferably, in step S1, the mass ratio of polymeric monomer, weather-resistant additive, and functional additive to anhydrous ethanol is 60-85:1-5:8-15:200-250.

[0007] Preferably, in step S1, the mass ratio of polymeric monomer, weather-resistant additive, and functional additive to anhydrous ethanol is 60-85:1-5:8-15:200-250.

[0008] Preferably, in step S1, the polymerizing monomer is composed of a silicon-based monomer, N-vinylpyrrolidone, and hydroxyethyl methacrylate in a mass ratio of 15-30:10-15:20-30.

[0009] Preferably, the silicon-based monomer is composed of 3-[tris(trimethylsiloxy)silyl]propyl vinylcarbamate, vinyltriisopropoxysilane, and polydimethylsiloxane monomethacrylate in a mass ratio of 60-75:20-30:25-32.

[0010] Preferably, the weather-resistant additive in step S1 is one or more of 2-hydroxy-4-methoxybenzophenone, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, and tris(2-hydroxy-4-octoxyphenyl)triazine.

[0011] Preferably, the functional additive in step S1 is one or more of hexafluorobutyl methacrylate, sulfobetaine methacrylate, and poly(N-isopropylacrylamide).

[0012] Preferably, in step S2, the mass ratio of the premixed solution, nano-silver, and nano-titanium dioxide is 100-120:0.3-0.5:1-3.

[0013] Preferably, in step S2, the crosslinking agent is composed of ethylene glycol dimethacrylate and pentaerythritol triacrylate in a mass ratio of 20-25:1-2.

[0014] Preferably, the amount of crosslinking agent added in step S2 is 0.1-1 wt% of the premixed solution.

[0015] Preferably, the initiator in step S2 is 2,2-dimethoxy-2-phenylacetophenone and / or phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0016] Preferably, the amount of initiator added in step S2 is 0.1-0.5 wt% of the premixed solution.

[0017] Preferably, the conditions for the photoinitiated polymerization reaction in step S2 are: a wavelength of 365 nm and a light intensity of 10-15 mW / cm².2 Ultraviolet light, photo-initiated polymerization reaction for 30-40 minutes.

[0018] A highly weather-resistant silicone hydrogel contact lens material is prepared by the above method.

[0019] In summary, this application has the following beneficial effects: This application selects three polysiloxane monomers: 3-[tris(trimethylsiloxy)silyl]propyl vinylcarbamate, vinyltriisopropoxysilane, and polydimethylsiloxane monomethacrylate. The 3-[tris(trimethylsiloxy)silyl]propyl vinylcarbamate molecule contains three trimethylsiloxy groups, and the silicon-oxygen segments provide continuous oxygen transport channels, improving the material's oxygen permeability. The carbamate groups enhance the compatibility of the siloxane with other monomers and reduce phase separation. Vinyltriisopropoxysilane acts as a crosslinking enhancer; the three isopropoxy groups, after hydrolysis, form silanol groups, which can undergo condensation reactions with other silicon-based monomers or nanoparticles to form a three-dimensional crosslinked structure, improving the material's mechanical properties. Furthermore, the silicon-oxygen crosslinked network after isopropoxy hydrolysis has strong hydrophobicity, reducing the swelling rate of the lens in water and maintaining dimensional stability. The three polysiloxane monomers, polydimethylsiloxane and polydimethylsiloxane monomethacrylate, serve as flexible segments. The long-chain polydimethylsiloxane imparts flexibility to the material, reduces rigidity, and improves wearing comfort. Furthermore, polydimethylsiloxane segments tend to migrate to the material surface, forming a low surface energy siloxane layer, which reduces protein adsorption and deposits, and improves anti-fouling performance.

[0020] This application combines silicon-based monomers and hydrophilic monomers. N-vinylpyrrolidone has strong polarity and can absorb a large amount of water, improving the lens's hydration and oxygen permeability. Hydroxyethyl methacrylate can provide moderate rigidity and toughness, synergistically improving the mechanical properties of the material with the silicon-based monomers. The three siloxane structures complement each other to form efficient oxygen channels. 2-hydroxy-4-methoxybenzophenone synergistically resists UV aging with silicon-oxygen bonds. Nano-TiO2 further enhances photostability and anti-degradation ability. Hexafluorobutyl methacrylate introduces fluorine, reducing surface energy and decreasing protein and lipid deposition. Detailed Implementation

[0021] The present application will be further described in detail below with reference to the embodiments.

[0022] N-vinylpyrrolidone used in the embodiments and comparative examples of this application was purchased from Shanghai Hongjun New Material Technology Co., Ltd.; hydroxyethyl methacrylate was purchased from Shandong Kejian Chemical Co., Ltd.; 3-[tris(trimethylsiloxy)silyl]propyl vinylcarbamate was purchased from Wuhan Kangqiong Biomedical Technology Co., Ltd.; vinyltriisopropoxysilane was purchased from Wuhan Kemike Biomedical Technology Co., Ltd.; and polydimethylsiloxane monomethacrylate was purchased from Shanghai Yongzheng Chemical Co., Ltd.

[0023] Examples 1-3 provide a high weather-resistant silicone hydrogel contact lens material and its preparation method.

[0024] Example 1 A method for preparing a highly weather-resistant silicone hydrogel contact lens material includes the following preparation steps: Step S1: Add the polymeric monomer, 2-hydroxy-4-methoxybenzophenone, and hexafluorobutyl methacrylate to anhydrous ethanol, stir in the dark for 1 hour at a stirring speed of 100 rpm, and after stirring evenly, a premixed solution is obtained. The mass ratio of the polymeric monomer, 2-hydroxy-4-methoxybenzophenone, hexafluorobutyl methacrylate, and anhydrous ethanol is 60:1:8:200. The polymeric monomer is composed of a silicon-based monomer, N-vinylpyrrolidone, and hydroxyethyl methacrylate in a mass ratio of 15:10:20. The silicon-based monomer is composed of 3-[tris(trimethylsiloxy)silyl]propyl vinylcarbamate, vinyltriisopropoxysilane, and polydimethylsiloxane monomethacrylate in a mass ratio of 60:20:25. Step S2: Add nano-silver and nano-titanium dioxide to the premixed solution, and after ultrasonic dispersion for 20 minutes (ultrasonic power 100W, ultrasonic frequency 40KHz), add crosslinking agent and initiator, mix evenly, and inject into the contact lens mold. Under inert gas protection, use a wavelength of 365nm and a light intensity of 10mW / cm². 2 The photo-initiated polymerization reaction was carried out under ultraviolet light for 30 minutes. After washing once with deionized water and equilibrating with borate buffer for 12 hours, a high weather-resistant silicone hydrogel contact lens material was obtained. The mass ratio of the premixed solution, nano-silver and nano-titanium dioxide was 100:0.3:1. The crosslinking agent consisted of ethylene glycol dimethacrylate and pentaerythritol triacrylate in a mass ratio of 20:1, and the amount of crosslinking agent added was 0.1 wt% of the premixed solution. The initiator was 2,2-dimethoxy-2-phenylacetophenone, and the amount of initiator added was 0.1 wt% of the premixed solution.

[0025] Example 2 A method for preparing a highly weather-resistant silicone hydrogel contact lens material includes the following preparation steps: Step S1: Add the polymeric monomer, 2-hydroxy-4-methoxybenzophenone, and hexafluorobutyl methacrylate to anhydrous ethanol, stir in the dark for 1.5 hours at a stirring speed of 150 rpm, and after stirring evenly, a premixed solution is obtained. The mass ratio of the polymeric monomer, 2-hydroxy-4-methoxybenzophenone, hexafluorobutyl methacrylate, and anhydrous ethanol is 75:3:12:230. The polymeric monomer is composed of a silicon-based monomer, N-vinylpyrrolidone, and hydroxyethyl methacrylate in a mass ratio of 25:12:25. The silicon-based monomer is composed of 3-[tris(trimethylsiloxy)silyl]propyl vinylcarbamate, vinyltriisopropoxysilane, and polydimethylsiloxane monomethacrylate in a mass ratio of 68:25:28. Step S2: Add nano-silver and nano-titanium dioxide to the premixed solution, and after ultrasonic dispersion for 25 minutes (ultrasonic power 120W, ultrasonic frequency 560KHz), add crosslinking agent and initiator, mix thoroughly, and inject into the contact lens mold. Under inert gas protection, use a wavelength of 365 nm and a light intensity of 12 mW / cm². 2 The photo-initiated polymerization reaction was carried out under ultraviolet light for 35 min. After washing twice with deionized water and equilibrating with borate buffer for 18 h, a high weather-resistant silicone hydrogel contact lens material was obtained. The mass ratio of the premixed solution, nano-silver and nano-titanium dioxide was 110:0.4:2. The crosslinking agent consisted of ethylene glycol dimethacrylate and pentaerythritol triacrylate in a mass ratio of 22:1.5, and the amount of crosslinking agent added was 0.5 wt% of the premixed solution. The initiator was 2,2-dimethoxy-2-phenylacetophenone, and the amount of initiator added was 0.3 wt% of the premixed solution.

[0026] Example 3 A method for preparing a highly weather-resistant silicone hydrogel contact lens material includes the following preparation steps: Step S1: Add the polymeric monomer, 2-hydroxy-4-methoxybenzophenone, and hexafluorobutyl methacrylate to anhydrous ethanol, stir in the dark for 2 hours at a stirring speed of 200 rpm, and after stirring evenly, a premixed solution is obtained. The mass ratio of the polymeric monomer, 2-hydroxy-4-methoxybenzophenone, hexafluorobutyl methacrylate, and anhydrous ethanol is 85:5:15:250. The polymeric monomer is composed of a silicon-based monomer, N-vinylpyrrolidone, and hydroxyethyl methacrylate in a mass ratio of 30:15:30. The silicon-based monomer is composed of 3-[tris(trimethylsiloxy)silyl]propyl vinylcarbamate, vinyltriisopropoxysilane, and polydimethylsiloxane monomethacrylate in a mass ratio of 75:30:32. Step S2: Add nano-silver and nano-titanium dioxide to the premixed solution, and after ultrasonic dispersion for 30 minutes (ultrasonic power 150W, ultrasonic frequency 60KHz), add crosslinking agent and initiator, mix evenly, and inject into the contact lens mold. Under inert gas protection, use a wavelength of 365 nm and a light intensity of 15mW / cm². 2 The photo-initiated polymerization reaction was carried out under ultraviolet light for 40 min. After washing three times with deionized water and equilibrating with borate buffer for 24 h, a high weather-resistant silicone hydrogel contact lens material was obtained. The mass ratio of the premixed solution, nano-silver and nano-titanium dioxide was 120:0.5:3. The crosslinking agent was composed of ethylene glycol dimethacrylate and pentaerythritol triacrylate in a mass ratio of 25:2, and the amount of crosslinking agent added was 1 wt% of the premixed solution. The initiator was 2,2-dimethoxy-2-phenylacetophenone, and the amount of initiator added was 0.5 wt% of the premixed solution.

[0027] Comparative Example 1 A method for preparing a highly weather-resistant silicone hydrogel contact lens material includes the following preparation steps: Step S1: Add the polymeric monomer, 2-hydroxy-4-methoxybenzophenone, and hexafluorobutyl methacrylate to anhydrous ethanol, stir in the dark for 1 hour at a stirring speed of 100 rpm, and after stirring evenly, a premixed solution is obtained. The mass ratio of the polymeric monomer, 2-hydroxy-4-methoxybenzophenone, hexafluorobutyl methacrylate, and anhydrous ethanol is 60:1:8:200. The polymeric monomer is composed of a silicon-based monomer and hydroxyethyl methacrylate in a mass ratio of 15:20. The silicon-based monomer is composed of 3-[tris(trimethylsiloxy)silyl]propyl vinylcarbamate, vinyltriisopropoxysilane, and polydimethylsiloxane monomethacrylate in a mass ratio of 60:20:25. Step S2: Add nano-silver and nano-titanium dioxide to the premixed solution, and after ultrasonic dispersion for 20 minutes (ultrasonic power 100W, ultrasonic frequency 40KHz), add crosslinking agent and initiator, mix evenly, and inject into the contact lens mold. Under inert gas protection, use a wavelength of 365nm and a light intensity of 10mW / cm². 2 The photo-initiated polymerization reaction was carried out under ultraviolet light for 30 minutes. After washing once with deionized water and equilibrating with borate buffer for 12 hours, a high weather-resistant silicone hydrogel contact lens material was obtained. The mass ratio of the premixed solution, nano-silver and nano-titanium dioxide was 100:0.3:1. The crosslinking agent consisted of ethylene glycol dimethacrylate and pentaerythritol triacrylate in a mass ratio of 20:1, and the amount of crosslinking agent added was 0.1 wt% of the premixed solution. The initiator was 2,2-dimethoxy-2-phenylacetophenone, and the amount of initiator added was 0.1 wt% of the premixed solution.

[0028] Comparative Example 2 A method for preparing a highly weather-resistant silicone hydrogel contact lens material includes the following preparation steps: Step S1: Add the polymeric monomer, 2-hydroxy-4-methoxybenzophenone, and hexafluorobutyl methacrylate to anhydrous ethanol, stir in the dark for 1 hour at a stirring speed of 100 rpm, and after stirring evenly, a premixed solution is obtained. The mass ratio of the polymeric monomer, 2-hydroxy-4-methoxybenzophenone, hexafluorobutyl methacrylate, and anhydrous ethanol is 60:1:8:200. The polymeric monomer is composed of a silane monomer and N-vinylpyrrolidone in a mass ratio of 15:10. The silane monomer is composed of 3-[tris(trimethylsiloxy)silyl]propyl vinylcarbamate, vinyltriisopropoxysilane, and polydimethylsiloxane monomethacrylate in a mass ratio of 60:20:25. Step S2: Add nano-silver and nano-titanium dioxide to the premixed solution, and after ultrasonic dispersion for 20 minutes (ultrasonic power 100W, ultrasonic frequency 40KHz), add crosslinking agent and initiator, mix evenly, and inject into the contact lens mold. Under inert gas protection, use a wavelength of 365nm and a light intensity of 10mW / cm². 2 The photo-initiated polymerization reaction was carried out under ultraviolet light for 30 minutes. After washing once with deionized water and equilibrating with borate buffer for 12 hours, a high weather-resistant silicone hydrogel contact lens material was obtained. The mass ratio of the premixed solution, nano-silver and nano-titanium dioxide was 100:0.3:1. The crosslinking agent consisted of ethylene glycol dimethacrylate and pentaerythritol triacrylate in a mass ratio of 20:1, and the amount of crosslinking agent added was 0.1 wt% of the premixed solution. The initiator was 2,2-dimethoxy-2-phenylacetophenone, and the amount of initiator added was 0.1 wt% of the premixed solution.

[0029] Comparative Example 3 A method for preparing a highly weather-resistant silicone hydrogel contact lens material includes the following preparation steps: Step S1: Add the polymeric monomer, 2-hydroxy-4-methoxybenzophenone, and hexafluorobutyl methacrylate to anhydrous ethanol, stir in the dark for 1 hour at a stirring speed of 100 rpm, and after stirring evenly, a premixed solution is obtained. The mass ratio of the polymeric monomer, 2-hydroxy-4-methoxybenzophenone, hexafluorobutyl methacrylate, and anhydrous ethanol is 60:1:8:200. The polymeric monomer is composed of a silicon-based monomer, N-vinylpyrrolidone, and hydroxyethyl methacrylate in a mass ratio of 15:10:20. The silicon-based monomer is composed of 3-[tris(trimethylsiloxy)silyl]propyl vinyl urethane and polydimethylsiloxane monomethacrylate in a mass ratio of 60:25. Step S2: Add nano-silver and nano-titanium dioxide to the premixed solution, and after ultrasonic dispersion for 20 minutes (ultrasonic power 100W, ultrasonic frequency 40KHz), add crosslinking agent and initiator, mix evenly, and inject into the contact lens mold. Under inert gas protection, use a wavelength of 365nm and a light intensity of 10mW / cm². 2 The photo-initiated polymerization reaction was carried out under ultraviolet light for 30 minutes. After washing once with deionized water and equilibrating with borate buffer for 12 hours, a high weather-resistant silicone hydrogel contact lens material was obtained. The mass ratio of the premixed solution, nano-silver and nano-titanium dioxide was 100:0.3:1. The crosslinking agent consisted of ethylene glycol dimethacrylate and pentaerythritol triacrylate in a mass ratio of 20:1, and the amount of crosslinking agent added was 0.1 wt% of the premixed solution. The initiator was 2,2-dimethoxy-2-phenylacetophenone, and the amount of initiator added was 0.1 wt% of the premixed solution.

[0030] Comparative Example 4 A method for preparing a highly weather-resistant silicone hydrogel contact lens material includes the following preparation steps: Step S1: Add the polymeric monomer, 2-hydroxy-4-methoxybenzophenone, and hexafluorobutyl methacrylate to anhydrous ethanol, stir in the dark for 1 hour at a stirring speed of 100 rpm, and after stirring evenly, a premixed solution is obtained. The mass ratio of the polymeric monomer, 2-hydroxy-4-methoxybenzophenone, hexafluorobutyl methacrylate, and anhydrous ethanol is 60:1:8:200. The polymeric monomer is composed of a silicon-based monomer, N-vinylpyrrolidone, and hydroxyethyl methacrylate in a mass ratio of 15:10:20. The silicon-based monomer is composed of 3-[tris(trimethylsiloxy)silyl]propyl vinylcarbamate and vinyltriisopropoxysilane in a mass ratio of 60:20. Step S2: Add nano-silver and nano-titanium dioxide to the premixed solution, and after ultrasonic dispersion for 20 minutes (ultrasonic power 100W, ultrasonic frequency 40KHz), add crosslinking agent and initiator, mix evenly, and inject into the contact lens mold. Under inert gas protection, use a wavelength of 365nm and a light intensity of 10mW / cm². 2 The photo-initiated polymerization reaction was carried out under ultraviolet light for 30 minutes. After washing once with deionized water and equilibrating with borate buffer for 12 hours, a high weather-resistant silicone hydrogel contact lens material was obtained. The mass ratio of the premixed solution, nano-silver and nano-titanium dioxide was 100:0.3:1. The crosslinking agent consisted of ethylene glycol dimethacrylate and pentaerythritol triacrylate in a mass ratio of 20:1, and the amount of crosslinking agent added was 0.1 wt% of the premixed solution. The initiator was 2,2-dimethoxy-2-phenylacetophenone, and the amount of initiator added was 0.1 wt% of the premixed solution.

[0031] Comparative Example 5 A method for preparing a highly weather-resistant silicone hydrogel contact lens material includes the following preparation steps: Step S1: Add the polymeric monomer, 2-hydroxy-4-methoxybenzophenone, and hexafluorobutyl methacrylate to anhydrous ethanol, stir in the dark for 1 hour at a stirring speed of 100 rpm, and after stirring evenly, a premixed solution is obtained. The mass ratio of the polymeric monomer, 2-hydroxy-4-methoxybenzophenone, hexafluorobutyl methacrylate, and anhydrous ethanol is 60:1:8:200. The polymeric monomer is composed of a silicon-based monomer, N-vinylpyrrolidone, and hydroxyethyl methacrylate in a mass ratio of 15:10:20. The silicon-based monomer is composed of 3-[tris(trimethylsiloxy)silyl]propyl vinylcarbamate, vinyltriisopropoxysilane, and polydimethylsiloxane monomethacrylate in a mass ratio of 60:20:25. Step S2: Add nano-silver and nano-titanium dioxide to the premixed solution, and after ultrasonic dispersion for 20 minutes (ultrasonic power 100W, ultrasonic frequency 40KHz), add crosslinking agent and initiator, mix evenly, and inject into the contact lens mold. Under inert gas protection, use a wavelength of 365nm and a light intensity of 10mW / cm². 2 The photo-initiated polymerization reaction was carried out under ultraviolet light for 30 minutes. After washing once with deionized water and equilibrating with borate buffer for 12 hours, a high weather-resistant silicone hydrogel contact lens material was obtained. The mass ratio of the premixed solution, nano-silver and nano-titanium dioxide was 100:0.3:1. The crosslinking agent was ethylene glycol dimethacrylate, and the amount of crosslinking agent added was 0.1 wt% of the premixed solution. The initiator was 2,2-dimethoxy-2-phenylacetophenone, and the amount of initiator added was 0.1 wt% of the premixed solution.

[0032] Performance testing The performance parameters of the high weather-resistant silicone hydrogel contact lens materials prepared in Examples 1-3 and Comparative Examples 1-5 of this application are as follows: Oxygen permeability coefficient: A 201T oxygen permeability meter (Creathch / Rehder-Dev Co., USA) was used, and the test was conducted using polarography according to the national standard GB / T 11417.7-2012. Among the parameters, D... k The unit is 10 -11 cm 2 / s·Pa; Visible light transmittance: Tested in accordance with national standard GB / T 11417.5-2012 "Ophthalmic Contact Lenses - Part 5: Test Methods for Optical Performance"; Mechanical properties: tested using an Instron mechanical testing machine; Aging resistance: Accelerated aging was performed for 48 hours at a temperature of 70℃ and a relative humidity of 75%, using an Instron mechanical testing machine. The test results are shown in Table 1.

[0033] Table 1. Overall performance of the contact lens materials prepared in Examples 1-3 and Comparative Examples 1-5

[0034] As shown in Table 1, the contact lens material prepared in this application not only has high oxygen permeability and light transmittance, effectively ensuring that the cornea obtains sufficient oxygen and maintains corneal health, but also does not produce foreign body sensation even after long-term wear. It also has excellent weather resistance, is not easily deformed or damaged, extends service life, reduces replacement frequency, and brings consumers an economical and convenient experience.

[0035] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the present invention in any form or substance. It should be noted that those skilled in the art can make several improvements and additions without departing from the present invention, and these improvements and additions should also be considered as protection of the present invention.

Claims

1. A method for preparing a high weather-resistant silicone hydrogel contact lens material, characterized in that, The preparation steps include the following: Step S1: Add the polymer monomer, weather-resistant additive, and functional additive to anhydrous ethanol, stir in the dark for 1-2 hours, and after stirring evenly, obtain the premixed solution. Step S2: Add nano silver and nano titanium dioxide to the premixed solution, disperse by ultrasonication, add crosslinking agent and initiator, mix evenly, inject into contact lens mold, carry out photo-initiated polymerization reaction under inert gas protection, wash with deionized water, and equilibrate with borate buffer to obtain high weather-resistant silicone hydrogel contact lens material. In step S1, the polymerizing monomer is composed of a silicon-based monomer, N-vinylpyrrolidone, and hydroxyethyl methacrylate in a mass ratio of 15-30:10-15:20-30. The silicon-based monomer is composed of 3-[tris(trimethylsiloxy)silyl]propyl vinylcarbamate, vinyltriisopropoxysilane and polydimethylsiloxane monomethacrylate in a mass ratio of 60-75:20-30:25-32. The weather-resistant additive in step S1 is one or more of 2-hydroxy-4-methoxybenzophenone, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, and tris(2-hydroxy-4-octoxyphenyl)triazine.

2. The method for preparing the high weather-resistant silicone hydrogel contact lens material according to claim 1, characterized in that, In step S1, the mass ratio of the polymer monomer, weather-resistant additive, functional additive and anhydrous ethanol is 60-85:1-5:8-15:200-250.

3. The method for preparing the high weather-resistant silicone hydrogel contact lens material according to claim 1, characterized in that, The functional additive in step S1 is one or more of hexafluorobutyl methacrylate, sulfobetaine methacrylate, and poly(N-isopropylacrylamide).

4. The method for preparing the high weather-resistant silicone hydrogel contact lens material according to claim 1, characterized in that, In step S2, the mass ratio of the premixed solution, nano-silver, and nano-titanium dioxide is 100-120:0.3-0.5:1-3.

5. The method for preparing the high weather-resistant silicone hydrogel contact lens material according to claim 1, characterized in that, In step S2, the crosslinking agent is composed of ethylene glycol dimethacrylate and pentaerythritol triacrylate in a mass ratio of 20-25:1-2; the initiator is 2,2-dimethoxy-2-phenylacetophenone and / or phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide.

6. The method for preparing the high weather-resistant silicone hydrogel contact lens material according to claim 1, characterized in that, The conditions for the photoinitiated polymerization reaction in step S2 are: a wavelength of 365 nm and a light intensity of 10-15 mW / cm². 2 Ultraviolet light, photo-initiated polymerization reaction for 30-40 minutes.

7. A method for preparing a high weather-resistant silicone hydrogel contact lens material according to any one of claims 1-6.

Citation Information

Patent Citations

  • High-hydrophilicity organic silicon hydrogel, corneal contact lens and preparation method

    CN112175130A

  • Preparation method of silicone hydrogel contact lenses convenient to demould

    CN116655852A